(untitled) (Economics and region, 2019)
The economy of Ukraine depends on the ability to adequately respond to the challenges of today that are manifested in energy-efficient changes in the economic, environmental, and social spheres of civil society. Practices of developed countries on types of energy saving policy are investigated, their peculiarities and possibilities of adaptation to Ukrainian realities are determined, principles of energy saving policy are developed and factors of state regulation of energy saving sphere are determined. The example of attracting grant funds, the implementation of which will raise the energy-efficient consciousness of our society, promote the idea of energy saving at the level of enterprises, self-government bodies is given. The practical implementation of the proposed developments on cooperation between Ukraine and the EU in the field of energy saving will ensure the formation of environmental interest of economic entities and authorities of different levels in the activation of energy efficient changes in the context of the implementation of the main guidelines for sustainable development of Ukraine.